Shadow Economy Management Strategies in Digital Business Ecosystems - Fauzi, Achmad; Nayyiroh, Frida Ulfatun; Aisyah, Siti; Laila, Nur; Abadi, Fitria (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2025)
In the form of an enormous shadow economy that lies outside the purview of formal regulations, the thriving digital economy of Indonesia is hesitant in traversing its path. This research will survey the strategy for managing informal activities in the digital business ecosystem, based on a survey of 300 respondents and interviews with 12 informants from five cities. The results revealed that 67% of participants engage in informal businesses, especially in e-commerce (38%), the gig economy (29%), and informal online services (21%). The logistic regression identified high legalization costs, low incentives, and a negative perception of the government as the key variables driving informality. Lower digital literacy was associated with lower informality, but the effect was not statistically significant. The research proposes a framework comprising three pillars to support formalization: digital platform governance, socioeconomic incentives, and data-driven technologies. The findings here inform the formulation of candidate policies for an inclusive, equitable, and sustainable digital economy in Indonesia.